2022
DOI: 10.1007/s00586-022-07292-x
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional paraspinal muscles in adult spinal deformity patients lead to increased spinal loading

Abstract: Purpose Decreased spinal extensor muscle strength in adult spinal deformity (ASD) patients is well-known but poorly understood; thus, this study aimed to investigate the biomechanical and histopathological properties of paraspinal muscles from ASD patients and predict the effect of altered biomechanical properties on spine loading. Methods 68 muscle biopsies were collected from nine ASD patients at L4–L5 (bilateral multifidus and longissimus sampled). The biopsies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…In an animal model of intervertebral disc degeneration, both multifidus muscle fibers and fiber bundles were stiffer 12 weeks after injury, 30 although in a model of spinal stiffness induced by ectopic calcification in ENT1‐deficient mice, reduced single fiber stiffness was observed, with no change in fiber bundle mechanics 31 . Interestingly, a recent study investigating passive mechanical properties of the multifidus muscle in individuals with adult spinal deformity demonstrated extremely high fiber bundle elastic modulus in some patients, resulting in increased simulated spinal compressive loads of over 500% 32 . Similar to our own data, this study reported histopathological findings of fibro‐fatty replacement and muscle degeneration in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal model of intervertebral disc degeneration, both multifidus muscle fibers and fiber bundles were stiffer 12 weeks after injury, 30 although in a model of spinal stiffness induced by ectopic calcification in ENT1‐deficient mice, reduced single fiber stiffness was observed, with no change in fiber bundle mechanics 31 . Interestingly, a recent study investigating passive mechanical properties of the multifidus muscle in individuals with adult spinal deformity demonstrated extremely high fiber bundle elastic modulus in some patients, resulting in increased simulated spinal compressive loads of over 500% 32 . Similar to our own data, this study reported histopathological findings of fibro‐fatty replacement and muscle degeneration in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…31 Interestingly, a recent study investigating passive mechanical properties of the multifidus muscle in individuals with adult spinal deformity demonstrated extremely high fiber bundle elastic modulus in some patients, resulting in increased simulated spinal compressive loads of over 500%. 32 T A B L E 1 Patient demographics of stratified by fatty atrophy and surgery status. The lower elastic modulus in individuals with severe fatty infiltration is, perhaps, not surprising given that adipocytes often accumulate in the interstitium, although our biopsy samples were carefully cleaned of extramuscular fatty tissue prior to passive mechanical testing.…”
Section: Passive Mechanical Properties In Pathological Musclementioning
confidence: 99%
“…Recent work demonstrated large variability in the active (specific force) and passive (elastic modulus) functional properties of paraspinal muscle biopsies from degenerative adult spinal deformity patients, reporting values that appear to be impaired compared to age-matched literature skeletal muscle norms 24 . Nonetheless, whether muscle alterations are consequences of spine degeneration and deformity or whether they precede, drive, or accompany the disorder progression is unknown; causative data are needed to address such hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…10 Atrophy of the PM can increase segmental instability, resulting in unbalanced load distribution during flexion and increase force transmission through the intervertebral disk, as demonstrated by finite element analysis. 11 This is assumed to accelerate degenerative processes once the regenerative capabilities are overtaxed, although limited clinical literature exists. 12 Inflammation and arthrogenic reflex inhibition due to degenerative processes have been associated with increased atrophy, 13,14 which complicates the causative analysis.…”
mentioning
confidence: 99%
“…Atrophy of the psoas muscle is typically described by a reduction in muscle area as the tendency for FI of the psoas muscle is less pronounced 10 . Atrophy of the PM can increase segmental instability, resulting in unbalanced load distribution during flexion and increase force transmission through the intervertebral disk, as demonstrated by finite element analysis 11 . This is assumed to accelerate degenerative processes once the regenerative capabilities are overtaxed, although limited clinical literature exists 12 .…”
mentioning
confidence: 99%